2008
DOI: 10.1051/0004-6361:200811150
|View full text |Cite
|
Sign up to set email alerts
|

Doppler factors, Lorentz factors and viewing angles for quasars, BL Lacertae objects and radio galaxies

Abstract: Aims. We have calculated variability Doppler boosting factors, Lorentz factors, and viewing angles for a large sample of sources by using total flux density observations at 22 and 37 GHz and VLBI data. Methods. We decomposed the flux curves into exponential flares and determined the variability brightness temperatures of the fastest flares. By assuming the same intrinsic brightness temperature for each source, we calculated the Doppler boosting factors for 87 sources. In addition we used new apparent jet speed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
498
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(557 citation statements)
references
References 53 publications
56
498
2
1
Order By: Relevance
“…Variability arguments (Jorstad et al 2005;Hovatta et al 2009) and kinematical analyses (Cohen et al 2015) yield a remarkably consistent value of 7.2 d = , from which we estimate a lower limit of the intrinsic brightness temperature in the core component of our RadioAstron observations of T b,int > 2.9 10 12 K. >´K, derived for the core component of the source structure described in Table 2 =´K is calculated from the data on the same baselines.…”
Section: Brightness Temperaturesupporting
confidence: 57%
See 1 more Smart Citation
“…Variability arguments (Jorstad et al 2005;Hovatta et al 2009) and kinematical analyses (Cohen et al 2015) yield a remarkably consistent value of 7.2 d = , from which we estimate a lower limit of the intrinsic brightness temperature in the core component of our RadioAstron observations of T b,int > 2.9 10 12 K. >´K, derived for the core component of the source structure described in Table 2 =´K is calculated from the data on the same baselines.…”
Section: Brightness Temperaturesupporting
confidence: 57%
“…In this model, the intrinsic brightness temperatures cannot exceed 10 11 -10 12 K (Kellermann & Pauliny-Toth 1969;Readhead 1994). Typical Doppler boosting is expected to be able to raise this temperature by a factor of ∼10 (see also Hovatta et al 2009;Lister et al 2013). For direct interferometric measurements, increasing the interferometer baseline length is the only way to measure higher brightness temperatures (see, e.g., Kovalev et al 2005), and hence, to place stringent observational constraints on the physics of the most energetic relativistic outflows.…”
Section: Introductionmentioning
confidence: 98%
“…However, compact blazars such as those in our sample, often exhibiting brightness temperatures exceeding the 5 × 10 10 K equipartition limit (Readhead 1994;, are known from VLBI observations to have Doppler boosting factors ranging from δ ∼ 5 to 30 (e.g., Hovatta et al 2009), with median values of δ ∼15 and 6 for FSRQs and BL Lac objects respectively. These sources are thus capable of exhibiting significant structural variations on timescales of a few months.…”
Section: Iss Intermittency and Intrinsic Variabilitymentioning
confidence: 94%
“…where a typical uncertainty of 0.4 dex and 0.2 dex is assigned for MTS of blazars (e.g., Vovk & Neronov 2013) and GRBs (e.g., Golkhou et al 2015), respectively, and a 50% or 30% error is introduced for Γ for GRBs (e.g., Lü et al 2012;Sonbas et al 2014) and blazars (e.g., Hovatta et al 2009), respectively. It is found that the global slope for blazars/GRBs is roughly consistent with that found in 21 GRBs only within uncertainties.…”
Section: Sonbasmentioning
confidence: 99%